2013
DOI: 10.1016/j.drugalcdep.2012.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and illicit substances: The moderating role of poverty

Abstract: Background Illicit substances increase risk of morbidity and mortality and have significant consequences for society. Personality traits are associated with drug use; we test whether these associations vary by socioeconomic status. Method Participants (N=412) from the Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) study completed the Revised NEO Personality Inventory and self-reported use of opiates and cocaine. 50% of participants were living below 125% of the federal poverty line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 26 publications
8
24
1
1
Order By: Relevance
“…Our study demonstrates strong correlations between personality profiles and the risk of drug use. This result supports observations from some previous [3,[12][13][14][16][17][18][19]. Individuals involved in drug use are more likely to have higher scores for N, and low scores for A and C .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study demonstrates strong correlations between personality profiles and the risk of drug use. This result supports observations from some previous [3,[12][13][14][16][17][18][19]. Individuals involved in drug use are more likely to have higher scores for N, and low scores for A and C .…”
Section: Discussionsupporting
confidence: 91%
“…Flory et al [14] found alcohol use to be associated with lower A and C, and higher E. They found also that lower A and C, and higher O are associated with marijuana use. Sutina et al [3] demonstrated that the relationship between low C and drug consumption is moderated by poverty; low C is a stronger risk factor for illicit drug usage among those with relatively higher socioeconomic status. They found that high N, and low A and C are associated with higher risk of drug use (including cocaine, crack, morphine, codeine, and heroin).…”
Section: Introductionmentioning
confidence: 99%
“…However, Brooner et al (2002) noted that when potentially confounding factors like mental disorders were controlled for, the personality traits most robustly differentiating people with opioid addiction from non-addicted peers were Conscientiousness, Agreeableness, and Excitement-seeking. In addition, Sutin et al (2013) examined the role of poverty in the relationships between personality traits and drugs. They concluded that high neuroticism and low agreeableness were related to drug use regardless of poverty status.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also successfully established a positive correlation between personality traits and the use of certain substances ( Anderson, Tapert, Moadab, Crowley, & Brown, 2007 ; Grekin, Sher, & Wood, 2006 ; Kornor & Nordvik, 2007 ; Prisciandaro, McRae-Clark, Moran-Santa Maria, Hartwell, & Brady, 2011 ; Terracciano, Lockenhoff, Crum, Bienvenu, & Costa, 2008 ). Individuals with high Neuroticism with negative emotions and low Agreeableness, and those who are undisciplined and disorganized (low Conscientiousness) are more likely to use substance than those who have opposite of these traits ( Sutin, Evans, & Zonderman, 2013 ).…”
Section: Introductionmentioning
confidence: 99%